Birth conditions nutritional status in childhood associated with cardiometabolic risk factors at 30 years of age: a cohort study - Vânia Pereira Oliveira; Mariane da Silva Dias; Natália Peixoto Lima; Bernardo Lessa Horta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: This study aimed to assess the association of birth conditions, nutritional status, and childhood growth with cardiometabolic risk factors at 30 years of age. We also evaluated whether body mass index (BMI) at 30 years mediated the association of weight gain in childhood with cardiometabolic risk factors. This is a prospective cohort study that included all live births in 1982 in hospitals in the city of Pelotas, Rio Grande do Sul State, Brazil, whose families lived in the urban area. Mothers were interviewed at birth, and participants were followed at different ages. For our analyses, we used data on weight and height collected at birth, 2 and 4 years and cardiovascular risk factors at 30 years. Multiple linear regressions were performed to obtain adjusted coefficients and G-formula for mediation analysis. Relative weight gain in childhood, despite the age, was positively related to mean arterial pressure, whereas relative weight gain in late childhood was positively associated with carotid intima-media thickness, pulse wave velocity, triglycerides, non-HDL cholesterol, plasma glucose, and C-reactive protein. BMI in adulthood captured the total effect of relative weight gain in the period between 2 and 4 years on carotid intima-media thickness, triglycerides, non-HDL cholesterol, and C-reactive protein. Our findings reinforce the evidence that rapid relative weight gain after 2 years of age may have long-term consequences on the risk of metabolic and cardiovascular disorders.